2013
DOI: 10.1097/qai.0b013e3182845d88
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Viral Hepatitis Is Associated With Low Bone Mineral Density in HIV-Infected Patients, ANRS CO 3 Aquitaine Cohort

Abstract: We found a high prevalence of low BMD overall, but chronic viral hepatitis was independently associated with osteoporosis only in female participants. Our data confirm the need of BMD evaluations for patients living with HIV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 28 publications
2
17
1
Order By: Relevance
“…No association between liver disease severity and BMD at any site was reported in co-infected patients by ElMaouche et al [15], despite the high histological evidence of cirrhosis (26%). Liver cirrhosis, assessed by liver biopsy or non-invasive methods (FibroScan and FibroTest), was also not found to be associated with decreased BMD in co-infected patients by Lawson-Ayayi et al [25]. In our study the extent of liver fibrosis, measured by transient elastography, was an independent predictor of bone loss in HIV/HCV co-infected patients in the femoral neck DXA Z-and T-scores.…”
Section: Discussionsupporting
confidence: 48%
See 1 more Smart Citation
“…No association between liver disease severity and BMD at any site was reported in co-infected patients by ElMaouche et al [15], despite the high histological evidence of cirrhosis (26%). Liver cirrhosis, assessed by liver biopsy or non-invasive methods (FibroScan and FibroTest), was also not found to be associated with decreased BMD in co-infected patients by Lawson-Ayayi et al [25]. In our study the extent of liver fibrosis, measured by transient elastography, was an independent predictor of bone loss in HIV/HCV co-infected patients in the femoral neck DXA Z-and T-scores.…”
Section: Discussionsupporting
confidence: 48%
“…The overall 26% prevalence of frank osteoporosis in our HIV-cohort was higher than the percentages reported in a previous meta-analysis and in other European case studies [1,3,24]. In our HIV/HCV co-infected patients osteoporosis prevalence was significantly higher than among HIV mono-infected subjects, in agreement with previous findings [25]. Many divergences persist regarding the prevalence of osteoporosis in HIV/HCV co-infection [14].…”
Section: Discussioncontrasting
confidence: 46%
“…Several cross-sectional studies in CHB-infected patients alone [9, 10] and among non-cirrhotic CHB- and chronic hepatitis C-infected patients [1114] have demonstrated that persons with CHB have reduced bone mineral density compared to uninfected individuals. A number of factors related to CHB infection have been hypothesized to contribute to low bone mineral density.…”
Section: Introductionmentioning
confidence: 99%
“…We performed tibial pQCT and whole-body DXA in ART-treated HIV/HCV-coinfected women compared with HCV-monoinfected women, ART-treated HIV-monoinfected women, and healthy women without a history of HIV infection or viral hepatitis. Our analyses focused on women because associations between HIV/HCV coinfection and low BMD have been stronger in women than in men [12,14]. We hypothesized that coinfected women would have lower trabecular volumetric BMD and cortical thinning due to endocortical bone loss, a pattern observed in other chronic inflammatory diseases [20][21][22], compared with HCV-or HIV-monoinfected women and those without a history of either infection.…”
mentioning
confidence: 99%
“…Despite the observed decrements in BMD [11][12][13][14] and increased fracture risk among HIV/HCV-coinfected individuals [10], the structural underpinnings and mechanisms for the skeletal fragility in these patients have not been established. Studies of BMD in coinfected patients have relied exclusively on dualenergy x-ray absorptiometry (DXA), a 2-dimensional projection technique that summarizes total trabecular and cortical bone mass within the projected bone area.…”
mentioning
confidence: 99%